The Problem of “Women’s Work” and the Idea of Work Democratization for the Liberating Empowerment of Women - Fathimah Fildzah Izzati (Jurnal Perempuan, 2019)
Women never make choices about their work democratically. In patriarchal society, “women’s work” is constructed as work that is in the area of social reproduction and is “natural” for women. Consequently, women are increasingly in a vulnerable position in the labor market. In addition, women also face obstacles to being actively involved in various democratic spaces such as unions and women’s movements, and wider social movements because they bear a double workload that is life-consuming. However, various women’s empowerment programs launched by a number of development institutions to overcome the problems faced by women turned out to be far from women’s interests. Empowerment, also known as “liberal empowerment”, actually depoliticized and atomized women. Feminist scholars also call for the importance of realizing “liberating empowerment”. Related to that, this paper sees that the process of democratization of work on women’s work is an effort that can be done to pave the way for women’s liberation.